To What Extent Do Borrower’s Factors, Lender’s Factors And Loan Factors Affect Loan Repayment? - Ghayad, Racha; Balouza, Mohamad; Zaraket, Mohammad (Journal of Ecohumanism, 2024)
The main objective of this research is the study the importance of credit risk management in every financial institution especially those who are loan grantors, that are suffering especially in poor and developing countries from high-rates of defaults, and all that is due to several factors that affect the customer commitment to repay the loan. The main objective of our research is to show the effect of credit risk management in minimizing credit risk and studying factors affecting customer’s commitment in financial institutions. Here was our problematic research: To what extent do borrower’s factors, lender’s factors and loan factors affect loan repayment? And by that many questions are related like: How dealing with these factors can be? And what is the role of credit risk management in studying and controlling these factors?.The method used to analyze and collect the data is quantitative descriptive analytical method using statistical tools. The result that are shown by the data collected at the end of the research show that a very high percentages of responds confirms that loan factors, borrower’s factors and lender’s factors affect clearly loan repayment and that credit risk management is absolute necessity. These results justify our main point and answer our problematic research about the importance of credit risk management in any financial institution.